Recent Advances on Piancatelli Reactions and Related Cascade Processes - Zhong, Sishi; Xu, Lei; Cai, Yunfei (Synthesis, 2021)
The Piancatelli reaction, which is the rearrangement of 2-furylcarbinol to cyclopentenone, involves a key furanoxonium ion intermediate and a furan ring opening-4π electrocyclization process. In recent years, the original oxa-Piancatelli reaction has been extended to a large family of aza- and carbo-Piancatelli reactions and related cascade processes, providing a powerful platform for the construction of diverse functionalized cyclopentenones and polycyclic cyclopentanones. Meanwhile, chiral Brønsted/Lewis acid based catalytic asymmetric approaches to Piancatelli reactions have also been achieved for the assembly of highly valued chiral cyclopentenone scaffolds. In this short review, we present an overview of the recent developments in these areas and focus primarily on reports published in the last five years.1 Introduction2 Diastereoselective Oxa-, Aza- and Carbo-Piancatelli Reactions3 Diastereoselective Cascade Piancatelli Reactions4 Asymmetric Piancatelli Reactions and Related Cascade Processes5 Miscellaneous Furanoxonium Ion-Based Rearrangements6 Conclusion
Keywords: Piancatelli reaction; furanoxonium ion; rearrangement; catalysis; functionalized cyclopentenone; diastereoselectivity; enantioselectivity